(NpXESY I WODEWILI (B/ s (N~ASTX (B4s - (N~EHOW(B, (NaNTON pAWLOWI^s ((NmOSKWA(B: s (NpRAWDA(B, s, 1984)
(Nw ^ETWERTYJ TOM sO^INENIJ a(B. (Np(B. (N~EHOWA WKL@^ENY PXESY I WODEWILI(B: "(N~AJKA(B", "(NtRI SESTRY(B", "(NwI[NEWYJ SAD(B", "(NsWADXBA(B" (NI DRUGIE(B.s
rus
Keywords: (NpXESYs; (NwODEWILIs